Pentingnya Pemanasan dalam Aktivitas Fisik dan Olahraga - Nimrot Manalu; Miftahul Ihsan; Bastian Lois; Nanda Hidayat; Juan Haga; Togu Hamonangan; Muhammad Tri; Berkat Simanjuntak; Fauzia Hany; Arif Rahman (CV. ITTC INDONESIA, 2025)
Warming up is an important component in every physical activity and sport that aims to prepare the body physiologically and psychologically before doing exercise or competition. Proper warming up can increase muscle temperature, increase flexibility, improve neuromuscular response, and reduce the risk of injury. This study aims to analyze the effectiveness of warming up in improving athletic performance and preventing injury based on literature reviews and previous research. The method used in this study is a literature review of various studies related to warming up, including types of warming up (general and specific warming up), optimal duration, and its impact on performance and safety in sports. The results of the study showed that warming up that combines light aerobic activity, dynamic stretching, and sport-specific movements can increase blood flow to the muscles, increase energy production, and accelerate the activation of the nervous system. In addition, warming up also helps in the mental preparation of athletes before competing or training.